Utilization of CT scanning associated with complex spine surgery. Issue 1 (December 2017) - Patel, Vikas; Andersson, Gunnar; Garfin, Steven; Resnick, Donald; Block, Jon
Abstract Background Due to the risk associated with exposure to ionizing radiation, there is an urgent need to identify areas of CT scanning overutilization. While increased use of diagnostic spinal imaging has been documented, no previous research has estimated the magnitude of follow-up imaging used to evaluate the postoperative spine. Methods This retrospective cohort study quantifies the association between spinal surgery and CT utilization. An insurance database (Humana, Inc.) with ≈ 19 million enrollees was employed, representing 8 consecutive years (2007–2014). Surgical and imaging procedures were captured by anatomic-specific CPT codes. Complex surgeries included all cervical, thoracic and lumbar instrumented spine fusions. Simple surgeries included discectomy and laminectomy. Imaging was restricted to CT and MRI. Postoperative imaging frequency extended to 5-years post-surgery. Results There were 140, 660 complex spinal procedures and 39, 943 discectomies and 49, 889 laminectomies. MRI was the predominate preoperative imaging modality for all surgical procedures (median: 80%; range: 73–82%). Postoperatively, CT prevalence following complex procedures increased more than two-fold from 6 months (18%) to 5 years (≥40%), and patients having a postoperative CT averaged two scans. For simple procedures, the prevalence of postoperative CT scanning never exceeded 30%. Conclusions CT scanning is used frequently for follow-up imaging evaluation following complex spine surgery. There is emerging evidence of an increased cancer risk due to ionizing radiation exposure with CT. In the setting of complex spine surgery, actions to mitigate this risk should be considered and include reducing nonessential scans, using the lowest possible radiation dose protocols, exerting greater selectivity in monitoring the developing fusion construct, and adopting non-ferromagnetic implant biomaterials that facilitate MRI postoperatively.